Grain-Based Dietary Background Impairs Restoration of Blood Flow and Skeletal Muscle During Hindlimb Ischemia in Comparison With Low-Fat and High-Fat Diets - Stafeev, Iurii; Boldyreva, Maria; Michurina, Svetlana; Mamontova, Elizaveta; Ratner, Elizaveta; Menshikov, Mikhail; Parfyonova, Yelena (Frontiers in Nutrition, 2022)
Background: Among vascular pathologies associated with obesity peripheral artery disease (PAD) occupies the important position. In clinical practice nutritional interventions are recommended for PAD patients. In this study we investigate how the different dietary backgrounds affect the regeneration rate of ischemic hindlimb in mice. Methods: Male C57BL/6J mice were housed on three types of diet: low-fat (LFD), high-fat (HFD) and grain-based diet (GBD) during 13 weeks. Metabolic parameters including FBG level, ITT and GTT were evaluated. The blood flow was assessed by laser Doppler scanning on 7, 14 and 21 days after hindlimb ischemia. Necrotic area of m.tibialis, macrophage infiltration, angiogenesis/arteriogenesis were evaluated by histology. Glucose uptake in recovered skeletal muscle was analyzed using [3H]-2-deoxyglucose; GLUT1 and GLUT4 expression were assessed by Western blotting. Results: In our work we developed three experimental groups with different metabolic parameters: LFD with normal glucose metabolism, GBD with mild hyperglycemia and HFD with impaired glucose tolerance. GBD-fed mice had a tendency to increased necrosis of m.tibialis and significantly higher macrophage infiltration than LFD and HFD groups. Moreover, GBD-fed mice had a trend to decreased blood flow recovery and significantly impaired arteriogenesis. Recovered skeletal muscle of GBD-fed mice had lower glucose uptake and decreased level of GLUT4 expression. Conclusion: Thus, we conclude that dietary background and metabolic status determine the rate of post-ischemic regeneration including angiogenesis, skeletal muscle recovery and metabolic activity. The most effective regeneration is supported by LFD, while the lowest rate of regeneration occurs on GBD.